Gamified Coffee Experiences: Unlocking Customer Citizenship Through Enjoyment and Engagement - Widi Dewi Ruspitasari; Rizka Zulfikar (Islamic University of Kalimantan MAB Banjarmasin, 2026)
This study investigated the role of gamification in fostering Customer Citizenship Behavior (CCB) within the digital coffee shop ecosystem in Malang City, East Java. The objective was to examine how gamification influenced CCB through perceived enjoyment and customer engagement, while digital literacy acted as a moderating variable. A quantitative research design was applied, and data were collected from 245 coffee enthusiasts who had experience using mobile applications integrated with gamified loyalty systems such as Fore Coffee and Kopi Kenangan. Structured questionnaires were distributed both online and offline, and responses were measured using a five-point Likert scale. The constructs included gamification, digital literacy, perceived enjoyment, customer engagement, and CCB. Data analysis was conducted using Structural Equation Modeling–Partial Least Squares (SEM-PLS), which tested direct, indirect, and sequential mediation effects, as well as moderation. The findings showed that gamification did not directly affect CCB but significantly enhanced perceived enjoyment, which subsequently increased customer engagement. Engagement emerged as the strongest predictor of CCB, confirming its role as a critical pathway for voluntary customer contributions. Digital literacy moderated the relationship between gamification and perceived enjoyment, indicating that user characteristics shaped how customers responded to gamified features.